Causes and impacts of northern North Atlantic freshening - Scheinert, Markus (2008)
The main focus of this study is on the variability of the freshwater budget in the subpolar North Atlantic. This region plays a crucial role in the large scale ocean circulation since the North Atlantic Deep Water (NADW) is formed here, which is an important part of the Meridional Overturning Circulation (MOC). Repeatedly appearing freshening events in the upper layer, known as 'Great Salinity Anomalies' during the 1970s, 80s and 90s, are hereby suspected to weaken the processes of deep water formation. Besides an increase of freshwater in the upper NADW, which is mainly fed by the Deep Convection in the Labrador Sea, there is also observational evidence for a freshening of the lower NADW. In this context, a large increase of the freshwater content in the subpolar basin and in the Nordic Seas has been found in observations between 1970 and 1995. However, the mechanisms that drive this freshening are still unclear. Numerous studies have investigated the variability of freshwater exports out of the Arctic, but only little is known about the exchange with the Atlantic south of the Subpolar Gyre. This study tries to close the gap for a better understanding of the deep water formation variability and the associated changes in the Meridional Overturning Circulation (MOC). Gegenstand dieser Studie ist die Variabilität des Süßwasserhaushaltes im subpolaren Nordatlantik, welchem durch die dort stattfindende Tiefenwasserbildung eine besondere Rolle in der meridionalen Umwälzbewegung des Ozeans zukommt. Dabei stehen immer wieder auftretende Süßwassersignale in der obersten Schicht des Nordatlantiks, die sog. großen Salzgehaltsanomalien der 1970er, 80er und 90er, im Verdacht, die Bildungsprozesse für das Tiefenwasser zu behindern. Neben einer Zunahme des Süßwassergehaltes im oberen Nordatlantischen Tiefenwasser (NADW), welches von Tiefenkonvektion in der Labradorsee gespeist wird, gibt es auch Hinweise aus Beobachtungen, dass der Salzgehalt des tiefen NADW ebenfalls abnimmt. In diesem Zusammenhang konnte für das subpolare ...